2001
DOI: 10.1046/j.1537-2995.2001.41020304.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HCV core antigen in HCV RNA positive, anti‐HCV negative blood donations from Polish blood donors

Abstract: Recent studies indicate that potentially infectious blood collected during a donor's anti-HCV-negative window period may be detected by testing for HCV RNA 1 or HCV core antigen. 2,3 HCV RNA mini-pool screening of blood donations for HCV by PCR was started in Poland at the beginning of 2000. All donations were screened for anti-HCV to eliminate anti-HCV reactive samples before the preparation of mini-pools. Testing for HCV RNA was accomplished in mini-pools of 48 prepared using a robotic sample processor (Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Such yield is considerably higher than that obtained in antibody-negative samples tested for HCV antigen or RNA or HIV RNA, which also have been implemented. [15][16][17] Anti-HBc screening, the alternative approach to HBV blood safety used in countries such as France, Germany, the United States, and Canada, could not be considered in Poland because the deferral of over 5% of anti-HBc-reactive donations would compromise the national blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such yield is considerably higher than that obtained in antibody-negative samples tested for HCV antigen or RNA or HIV RNA, which also have been implemented. [15][16][17] Anti-HBc screening, the alternative approach to HBV blood safety used in countries such as France, Germany, the United States, and Canada, could not be considered in Poland because the deferral of over 5% of anti-HBc-reactive donations would compromise the national blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of fluctuating detectability of viral genome and neutralizing antibody was seen in samples from donors 7 through 13 (Table 3). A second large group of donors (15)(16)(17)(18)(19)(20)(21)(22) was characterized by the repeated detection of HBV DNA at low concentration (Ͻ1,000 IU/ mL; in most cases, Ͻ200 IU/mL) without detectable antiHBs. Anti-HBc, often associated with anti-HBe, was consistently detected.…”
mentioning
confidence: 99%
“…It has been demonstrated that the potential risk of transfusion-associated infection may be reduced significantly by screening for circulating HCV core antigen (HCVcAg) [Couroucé et al, 2000;Peterson et al, 2000;Brojer et al, 2001;Icardi et al, 2001;Lee et al, 2001;Piccoli et al, 2001], before the appearance of anti-HCV antibody. The diagnostic value of this assay has been limited by the relative lack of sensitivity observed in anti-HCV-positive specimens.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have shown that they can shorten the window period. Therefore, this was applied in blood testing to enhance the overall effectiveness of serological HCV screening in some countries [101][102][103]. However, the Global Database on Blood Safety shows that testing with anti-HCV ELISA is insufficient, particularly in countries with a low human development index-only 51.3 % of units of blood are tested for HCV [104].…”
Section: Blood Safetymentioning
confidence: 99%